Charting Thoughts Essays on Art in Southeast Asia - Low, Sze Wee (National Gallery Singapore, 2018)
A constellation of thoughts by 25 established and emerging scholars who plot the indices of modernity and locate new coordinates within the shifting landscape of art. These newly commissioned essays are accompanied by close to 200 full-colour image plates.